Training and its effect in quality management in organizations - Parra-Penagos, Carlos; Rodríguez-Fonseca, Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article is approached from the view of management sciences. The goal was to make a review of the training and its effect on quality management within organizations. Initially, some backgrounds related to quality and training are proposed. Subsequently, a conceptualization of training as a way of education in the organization is done, and finally, it focuses on training based on the quality management in organizations. It was concluded that training directly affects the quality from the development of knowledge, skills and abilities, contributing to the development of quality systems in the organization.